Clinical characteristics and outcome of tibial pilon fractures treated with open reduction and plating in a tertiary medical college - Das, Manoj; Pandey, Suresh; Gupta, Hemant Kumar; Bidary, Suraj; Das, Anilata (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Tibial pilon fracture possess a challenge to achieve optimum outcome because of soft tissue related complications and intra-articular nature of the fracture. Surgical treatments and outcomes vary in literature. The objective of this study was to assess the functional and radiological outcome of tibial pilon fractures treated with open reduction and internal fixation with plate and screws.Methods: This was a descriptive study of retrospective data of displaced tibial pilon fractures treated with open reduction and internal fixation with plate and screws. Functional outcome was assessed by American Orthopaedic Foot and Ankle Society (AOFAS) score and fracture union with plain radiography.Results: There were total of 20 cases of tibial pilon fractures with mean age of 41.4 years (SD±14.36). The mean AOFAS score was 81.60 (range 42-100) at mean follow up of 18.2 months (range 9-48). Good to excellent results was found in 12(60%) and fair results in 6(30%) cases. All the fractures united at mean of 5.8 months (range 5-7). Partial wound dehiscence was seen in 1(5%) case and marginal skin necrosis occurred in 3(15%) of the cases.Conclusions: Current study showed favorable radiological and functional outcome in most of the tibial pilon fractures treated with open reduction and internal fixation with plate and screws with acceptable rate of minor wound related complications